Gene by Neuroticism Interaction and Cognitive Function among Older Adults - Dar-Nimrod, Ilan (2012)
OBJECTIVES: Both ApoE (apolipoprotein E) ε-4 allele(s) and elevated trait neuroticism, the tendency to experience distress, are associated with cognitive function among older adults. We predicted that neuroticism moderates the association between ApoE and cognitive function and also explored whether other personality dimensions (openness to experience, agreeableness, extraversion, and conscientiousness) affect the association between ApoE status and cognitive function. METHOD: Five-hundred and ninety-seven older adults (mean age of 78) enrolled in the Ginkgo Evaluation of Memory (GEM) study completed the NEO-Five Factor Inventory of personality. Cognitive function was assessed via the cognitive portion of the Alzheimer’s Disease Assessment Scale (ADAS-cog), and a blood sample for ApoE genotyping was drawn. RESULTS: As hypothesized, regression analysis indicated that neuroticism moderated the relationship between the presence of ApoE ε-4 and cognitive function. Individuals with high neuroticism scores had significantly lower ADAS-cog scores compared with individual with low neuroticism scores, but this was true only among carriers of ApoE ε-4 (interaction effect β = .124, p = .028). There was scant evidence that other personality dimensions moderate the association between ApoE ε-4 and cognitive function. CONCLUSIONS: Cognitive function may be affected by ApoE and neuroticism acting in tandem. Research on the underlying physiological mechanisms by which neuroticism amplifies the effect of ApoE ε-4 is warranted. The study of genotype by phenotype interactions provides an important and useful direction for the study of cognitive function among older adults and for the development of novel prevention programs.